Increasing Paddy and Tuber Crop Production Through Environmentally Friendly Straw Biodecomposer Technology Innovation in Wara Village, Jayawijaya - Hasriani M; Tiomy Butsianto Adi; Siti Latifa Wulandari; Herlyani S; Reynaldi Laurenze; Enjelin Delila Yare; Kiliopas Walilo; Yulianus Kepno; Ikranul Sudarwan; Clara Irianti Natalia Maresyembun; Olivia Natasya Matuan; Elsye Eva Weya; Mince Bahabol; Natalia Ledi Sirwa; Miel Amohoso; Periska Degey; Fringki Wolom; Beti Elopere; Omega Bogum; Agus Logo; Fajar Sidik Asso; Deli Yikwa; Diana Yikwa; Yeriana Aud; Viktor Tabuni (Unram Journal of Community Service, 2025)
Rice straw management remains a major challenge in Wara Village, Jayawijaya Regency, where farmers commonly burn straw after harvest and lack the technical capacity to process agricultural waste. This community service program aimed to strengthen farmers’ and women’s family welfare development (FWD) technical and managerial skills by introducing biodecomposer technology based on locally available resources. The program involved socialization, technical training on compost production, simple farm bookkeeping instruction, field practice using molasses and EM4, and intensive mentoring. The results indicated substantial improvements in participants' knowledge and skills, including the ability to process 20–30 kg of rice straw per fermentation cycle and the establishment of a pilot farmer group capable of independently applying the technology. The family welfare development also gained competencies as household-level environmental stewards. The intervention contributed to reducing straw burning, improving soil quality through organic matter reintegration, and strengthening local socio-economic institutions. Overall, this program supports the development of autonomous, environmentally friendly, and sustainable agricultural practices in Wara Village.